2001
DOI: 10.1163/156853801750096213
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal activity of snakes in the Atlantic forest in southeastern Brazil

Abstract: Seasonal abundance of some snake species from the Atlantic forest in southeastern Brazil was inferred from collection data gathered throughout twelve years at the Instituto Butantan in São Paulo, Brazil. The number of collected individuals of Chironius spp., Liophis miliaris, Spilotes pullatus, Tropidodryas spp., Micrurus corallinus, and Bothrops jararaca was significantly higher during the rainy season, whereas the number of Sibynomorphus neuwiedi was higher during the dry season. Erythrolamprus aesculapii, X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 18 publications
(23 reference statements)
3
40
0
3
Order By: Relevance
“…No Núcleo Santa Virgínia, a variação sazonal de temperatura é claramente percebida, com temperaturas sensivelmente mais baixas de maio a setembro. Fatores bióticos como disponibilidade de presas e época reprodutiva também podem ser responsáveis por diferenças na taxa de encontro de serpentes ao longo do ano (Marques 1998, Marques et al 2000. Espécies de serpentes batracófagas ( Chironius spp.…”
Section: Atividade Sazonalunclassified
“…No Núcleo Santa Virgínia, a variação sazonal de temperatura é claramente percebida, com temperaturas sensivelmente mais baixas de maio a setembro. Fatores bióticos como disponibilidade de presas e época reprodutiva também podem ser responsáveis por diferenças na taxa de encontro de serpentes ao longo do ano (Marques 1998, Marques et al 2000. Espécies de serpentes batracófagas ( Chironius spp.…”
Section: Atividade Sazonalunclassified
“…As a result of its association with movements, activity may vary depending on gender, age, reproductive condition, or molting (Duvall et al 1985, Macartney et al 1988. Unlike in temperate areas, in most tropical regions, the winter, even the most harsh, does not seem to prevent the activity of most ectotherms, which tend to remain active throughout the year (Marques et al 2000, Tozetti et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…In in tropical areas of South America, snake assemblages have shown activity peaks during the warmer, rainy season (mid-spring to early autumn; Marques et al 2000, Maciel et al 2003. The rattlesnake Crotalus durissus, however, exhibits a peak of activity in the dry/colder season (autumn) (Salomão et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we found that both species C. durissus and B. jararaca have similar patterns of annual activity (18,19). There are two activity peaks, one at the transition from summer to fall, related to mating season, in which both males and females are active.…”
Section: Discussionmentioning
confidence: 81%